Economic value and function of trades unions - Deaver, Bernice (My University, 1908)
Introduction: Trade unions were first organized in England. These like the guilds sprang up as a defense against the capitalist combinations and associations resembling trade societies existed in England before fifteen hundred and sixty two, but the existence of a continuous association of wage earners for the purpose of improving the conditions of their employment did not exist until about the year seventeen hundred.
Citation: Deaver, Bernice. Economic value and function of trades unions. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Trade; Unions; Capitalism; Guilds; Graduating theses; Senior theses; Theses